Analisis Pertumbuhan Industri Manufaktur Berdasarkan Skala Usaha di Indonesia - Salsabila Agustina G; Anggita Aznabia F; Naufal Reihan H.P; Ajril Zulfa Mardiya (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
The manufacturing sector in Indonesia constitutes a fundamental element of the national economy, contributing around 20 percent to the gross domestic product in 2022. This investigation explores differences in manufacturing output according to business scales—micro, small, medium, and large—with an emphasis on Java Island, which accounts for more than 60 percent of national manufacturing activities. The principal objectives encompass examining output growth trends, determining the leading scale in output contributions, assessing productivity variations across scales, and evaluating the effects of labor, investment, and scale variables on output. Applying panel data regression via the random effect model to secondary data from the Central Bureau of Statistics spanning 2015 to 2022, the study incorporates robustness evaluations to consider pandemic impacts. Core results demonstrate that large-scale entities prevail in output and exhibit elevated productivity, supported by superior access to investment and labor resources. These results suggest policy directions for equitable resource distribution to promote holistic sectoral progress. The research highlights the importance of specific interventions to address imbalances in smaller scales.